Follicular fluid dehydroepiandrosterone sulfate is a credible marker of oocyte maturity and pregnancy outcome in conventional in vitro fertilization cycles - Natachandra M Chimote; Nirmalendu M Nath; Nishad N Chimote; Bindu N Chimote (Wolters Kluwer Medknow Publications, 2015)
Aim: To investigate if the level of dehydroepiandrosterone sulfate (DHEA-s) in follicular fluid (FF) influences the competence of oocytes to fertilize, develop to the blastocyst stage, and produce a viable pregnancy in conventional in vitro fertilization (IVF) cycles. Settings and Design: Prospective study of age-matched, nonpolycystic ovary syndrome (PCOS) women undergoing antagonist stimulation protocol involving conventional insemination and day 5 blastocyst transfer. Materials and Methods: FF levels of DHEA-s and E2 were measured by a radio-immuno-assay method using diagnostic kits. Fertilization rate, embryo development to the blastocyst stage and live birth rate were main outcome measures. Cycles were divided into pregnant/nonpregnant groups and also into low/medium/high FF DHEA-s groups. Statistical analysis was done by GraphPad Prism V software. Results: FF DHEA-s levels were significantly higher in pregnant (n = 111) compared to nonpregnant (n = 381) group (1599 ± 77.45 vs. 1372 ± 40.47 ng/ml; P = 0.01). High (n = 134) FF DHEA-s group had significantly higher percentage of metaphase II (MII) oocytes (91.5 vs. 85.54 vs. 79.44%, P < 0.0001), fertilization rate (78.86 vs. 74.16 vs. 71.26%, P < 0.0001), cleavage rate (83.67 vs. 69.1 vs. 66.17%, P = 0.0002), blastocyst formation rate (37.15 vs. 33.01 vs. 26.95%, P < 0.0001), and live birth rate (29.85 vs. 22.22 vs. 14.78%, P = 0.017) compared to medium (n = 243) and low (n = 115) FF DHEA-s groups, respectively despite comparable number of oocytes retrieved and number of blastocysts transferred. FF DHEA-s levels correlated significantly with the attainment of MII oocytes (Pearson r = 0.41) and fertilization rates (Pearson r = 0.35). Conclusion: FF DHEA-s level influences the oocyte maturation process and is predictive of fertilization, embryo development to the blastocyst stage and live birth rates in non-PCOS women undergoing conventional IVF cycles.